2021
DOI: 10.1016/j.ajem.2021.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Intubation rate of patients with hypoxia due to COVID-19 treated with awake proning: A meta-analysis

Abstract: Background: Awake prone positioning (PP), or proning, is used to avoid intubations in hypoxic patients with COVID-19, but because of the disease's novelty and constant evolution of treatment strategies, the efficacy of awake PP is unclear. We conducted a meta-analysis of the literature to assess the intubation rate among patients with COVID-19 requiring oxygen or noninvasive ventilatory support who underwent awake PP. Methods: We searched PubMed, Embase, and Scopus databases through August 15, 2020 to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 60 publications
0
29
1
Order By: Relevance
“…In a review study by da Silva et al, intubation need vary from 42% to 47% (68). Besides, Cardona et al reported that the intubation rate was 28% among hypoxic COVID-19 patients (69). This discrepancy in statistics may be due to the variety of study populations, study environments, or intubation criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In a review study by da Silva et al, intubation need vary from 42% to 47% (68). Besides, Cardona et al reported that the intubation rate was 28% among hypoxic COVID-19 patients (69). This discrepancy in statistics may be due to the variety of study populations, study environments, or intubation criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In the review study by da Silva CM et al, intubation need vary from 2, 3, 4, to 42% and 47% [55]. Besides, Cardona et al reported that the intubation rate was 28% among hypoxic COVID-19 patients [56]. This discrepancy in statistics may be due to the variety of study population, study environment, or intubation criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygenation improvement was sustained after re-supination in patients in whom the prone position was combined with noninvasive respiratory strategies (HFNO or NIV) [ 117 , 126 ]. Overall, around 28% of patients eventually required invasive MV [ 131 , 132 , 133 ]. It remains inconclusive whether awake self-proning had an effect on intubation and mortality.…”
Section: Prone Position During High-flow Nasal Oxygen or Noninvasive Ventilation In Patients With Covid-19mentioning
confidence: 99%